PEMAKNAAN BAHASA ISYARAT SUKU METKAYINA DALAM FILM AVATAR THE WAY OF WATER - yunika glory sun kase; Monika Wutun; Henny L. L. Lada (Jurnal Ranah Komunikasi, 2025)
The film Avatar The Way of Water contains the use of sign language in communication which is interesting for researchers to conduct research with the aim of analyzing the meaning of sign language among the Metkayina tribe and with the Tulkun sea animal using Ferdinand de Saussure's semiotic method. The results of the study found that there are meanings of discrimination and cultural diversity due to the lack of understanding of sign language as a migrant tribe, as well as cooperation when hunting in the water by fellow nations in the Metkayina tribe. Other meanings found in this film are requests for help, friendship, and joking as closeness, gratitude, affirmation of friendship, care, trust, as well as greetings and exchanging news through spiritual connections when the Metkayina tribe communicates with Tulkun. The conclusion of this study is that there are 7 signifiers and signifieds, 5 forms and content, 2 langue and parole relationships, 2 synchronic and diachronic relationships, and 3 syntagmatic and associative relationships in sign language communication among the Metkayina tribe as well as 5 nonverbal movements as signifiers and signifieds, 6 gestures as form and content, 2 langue and parole relationships, 2 synchronic and diachronic relationships, and 3 syntagmatic and associative relationships when the Metkayina tribe communicates with the sea animal Tulkun. Researchers hope that further research can reveal the meaning of the use of sign language not only in films but in everyday life.